Higher Education and Social Inequalities - Waller, Richard, author.
1 online resource
Keywords: "A university education has long been seen as the gateway to upward social mobility for individuals from lower socio-economic backgrounds, and as a way of reproducing social advantage for the better off. With the number of young people from the very highest socio-economic groups entering university in the UK having effectively been at saturation point for several decades, the expansion witnessed in participation rates over the last few decades has largely been achieved by a modest broadening of the base of the undergraduate population in terms of both social class and ethnic diversity. However, a growing body of evidence exists in the continuation of unequal graduate outcomes. This can be seen in terms of employment trajectories in the UK. The issue of just who enjoys access to which university, and the experiences and outcomes of graduates from different institutions remain central to questions of social justice, notably higher education's contribution to social mobility and to the reproduction of social inequality. This collection of contemporary original writings explores these issues in a range of specific contexts, and through employing a range of theoretical and methodological approaches. The relationship between higher education and social mobility has probably never been under closer scrutiny. This volume will appeal to academics, policy makers, and commentators alike. Higher Education and Social Inequalities is an important contribution to the public and academic debate."--Provided by publisher.